Association Between Dietary Patterns, Physical Activity, and BMI with Hypertension Among Rural Indonesian Farmers: A Cross Sectional Study Using a Nutritional Ecology Perspective - Syamsul Alam; Habibi Habibi; Nildawati Nildawati; Syarfaini Syarfaini; Nurfaidah Nurfaidah; Isymiarni Syarif (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Hypertension is a major non-communicable disease with a high prevalence in Indonesia, particularly in rural areas. Although farmers are generally engaged in physical labor, lifestyle factors such as unhealthy dietary patterns and poor nutritional status may contribute to elevated blood pressure. The existing literature has yet to fully integrate dietary patterns, physical activity, and BMI within a nutritional ecology framework to understand hypertension among rural farming populations; this study addresses that gap.This study aimed to analyze the association between dietary patterns, physical activity, and Body Mass Index/BMI (nutritional status) with hypertension among farmers in Kanreapia Village, Indonesia. Methods: A cross-sectional study was conducted involving 908 farmers aged 35–59 years, selected through simple random sampling. Data were collected via structured interviews and measurements of blood pressure and anthropometry. Data analysis included univariate, bivariate (Chi-Square test), and multivariate analysis using logistic regression. Results: The prevalence of hypertension among respondents was 51.2%. Bivariate analysis showed significant associations between age, smoking habits, risky dietary patterns (such as consumption of salty foods, grilled foods, processed meats, and instant noodles), and BMI with hypertension (p< 0.05). However, multivariate analysis identified only nutritional status (BMI) as significantly associated with hypertension (p < 0.001; OR = 0.41; CI: 0.508–0.809). Other variables were not statistically significant, including salty food consumption (OR = 0.999; CI: 0.758–1.316), grilled foods (OR = 0.963; CI: 0.613–1.514), processed meat/chicken/fish with preservatives (OR = 1.202; CI: 0.774–1.866), instant foods (OR = 0.957; CI: 0.729–1.255), and fruit consumption as a fiber source (OR = 1.124; CI: 0.847–1.491). Conclusion: Nutritional status is the main determinant of hypertension among farmers, even though risky dietary patterns and physical activity showed significant associations in bivariate analysis. Public health interventions focusing on weight management and nutrition education are essential to reduce hypertension risk in rural farming communities.